E-227 Feasibility of robotic-assisted neuroendovascular procedures. (4th August 2020) - Mendes Pereira, V; Cancelliere, N; Nicholson, P; Radovanovic, I; Turk, A; Sungur, J; Krings, T
Abstract : Background: Global geographic inequity exists in access to advanced neuroendovascular procedures for the management of acute ischemic stroke and aneurysmal subarachnoid hemorrhage. Robotic technologies may enable long-distance tele-stroke intervention in the future. This study assessed the feasibility of a robotic-assisted system for neuroendovascular intervention. Methods: In this clinical case series, we used the assistance of a CorPath GRX Neuroendovascular Robotic System, (Corindus, A Siemens Healthineers Company, Waltham, MA USA) to perform intracranial, endovascular procedures in 6 patients with complex, wide-necked intracranial saccular aneurysms. We evaluated technical success, periprocedural complications, and need for conversion to manual procedures. Findings: Between November 2019 and February 2020, we treated six patients (five female) ranging from 63 to 84 years old. All procedures were successful with no complications or changes in baseline neurological status. There were no conversions to manual required for the procedures. Team communication and collaboration were excellent, even without line of sight between the bedside team and the primary operator of the robotic controls. Interpretation: We have demonstrated initial feasibility and safety of remote-controlled, robotic-assisted intervention during neuroendovascular procedures. This case series represents an incremental but important step toward the eventual realization of long-distance stroke care and geographic equalization of access to advance neuroendovascular procedures. Disclosures: V. Mendes Pereira: None. N. Cancelliere: None. P. Nicholson: None. I. Radovanovic: None. A. Turk: 5; C; CORINDUS - SIEMENS HEALTHNEERS COMPANY. J. Sungur: 5; C; CORINDUS - SIEMENS HEALTHNEERS COMPANY. T. Krings: None.